Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I can faintly visualize some way of deducing this formula with exponential functions but forgot it. How do you remember it? Suppose you just forget whether it is plus-or-minus there, how do you find the right formula now? Use pythagoras and?

share|cite|improve this question
up vote 9 down vote accepted

One approach is to remember that $\cosh x = \cos(ix)$ and $\sinh x = -i \sin (ix)$, which reduces this to $\sin^2 z + \cos^2 z = 1$.

share|cite|improve this answer
Bonus: For the purposes of this identity, you don't even have to remember whether or not there's a minus sign in $\sinh x = -i \sin(ix)$. – Nate Eldredge Feb 10 '12 at 3:50

Maybe this will help as a mnemonic.

The functions $\cosh$ and $\sinh$ are to the (right half of) the hyperbola $x^2-y^2=1$ as $\cos$ and $\sin$ are to the circle $x^2+y^2=1$. Or, more sloppily, $\cosh$ ($\cos$) is $x$ and $\sinh$ ($\sin$) is $y$.

By that I mean that the standard trigonometric parametrization of the unit circle is $$x=\cos t\qquad y=\sin t.$$

A standard parametrization of the right half of the rectangular hyperbola $x^2-y^2=1$ is $$x=\cosh t\qquad y=\sinh t.$$

Remark: I like $\cos^2\theta+\sin^2\theta=1$ better than $\sin^2\theta+\cos^2\theta=1$. After all, $x$ comes before $y$.

share|cite|improve this answer
Nitpick: The functions $\cosh$ and $\sinh$ are to the right half of the hyperbola $x^2 - y^2 = 1$... – Rahul Jan 28 '12 at 21:26

The derivation is of the form (see that this checks out yourself)


If $ab=1$ then we get the formula, specifically when $a=e^x$ and $b=e^{-x}$ and then the squares above are the two hyperbolic trig functions. This is just plugging in definitions and computing, that's all.

share|cite|improve this answer

remember $(a+b)^2-(a-b)^2=4ab$ and $e^xe^{-x}=1$

share|cite|improve this answer

If you’re visually oriented, try remembering the shapes of the graphs for $x\ge 0$, together with that of $y=e^x$: they’re very similar, they get closer together as $x$ increases, and $e^x$ is squeezed in above $\operatorname{sinh}x$ and below $\operatorname{cosh}x$. Since they’re blowing up, $\operatorname{cosh}^2 x+\operatorname{sinh}^2 x$ can’t be constant, and since $\cosh x>\sinh x\ge 0$, $\operatorname{sinh}^2 x-\operatorname{cosh}^2 x$ can’t be $1$. That leaves only the right choice, $\operatorname{cosh}^2 x-\operatorname{sinh}^2 x=1$.

If you’re not visually oriented, my advice is simply to learn the exponential formulas and think of the identity in the way suggested by anon in his answer.

share|cite|improve this answer


$$\cos(ix)^2 + \sin(ix)^2 = 1$$

$$\cosh(x)^2 + i^2 \sinh(x)^2 = 1$$

$$\cosh(x)^2 + i^2 \sinh(x)^2 = 1$$

$$\cosh(x)^2 -\sinh(x)^2 = 1$$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.